Crosslinked polybenzimidazole membrane as well as preparation method and application thereof
By introducing crosslinking agents and pore-forming agents into the polybenzimidazole membrane, a three-dimensional network structure is formed, which solves the problem of insufficient mechanical strength and conductivity of the PBI membrane material, and realizes efficient liquid flow battery separator performance, simplifies the Preparation process and reduce costs.
Patent Information
- Application Number
- CN202411422612.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-10
AI Technical Summary
The existing polybenzimidazole (PBI) film materials have poor elongation of break, low conductivity, and complex preparation methods and high cost, which limits their wide application in flow batteries.
The crosslinked polybenzimidazole membrane is adopted to form a three-dimensional network structure by selecting suitable crosslinking agents and pore-forming agents, which improves mechanical strength and proton conductivity, simplify the preparation process and reduces costs.
A cross-linked polybenzimidazole film with high mechanical strength, low electrolyte swelling rate and high durability has been achieved, which significantly improves electrochemical performance and mechanical stability. It is suitable for liquid flow batteries, with Coulombic efficiency and energy efficiency reaching 99% and above.
Smart Images

Figure CN119297321A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of liquid flow batteries, and in particular relates to a cross-linked polybenzimidazole membrane and a preparation method and application thereof. Background Art
[0002] In the exploration of modern and efficient energy storage systems, flow batteries have become the focus of research and industry due to their unique advantages. This type of battery system can independently optimize power and energy, and can easily expand its energy storage capacity by increasing the amount of electrolyte, which is particularly suitable for large-scale energy storage applications, such as grid energy storage and balancing of renewable energy systems.
[0003] However, the development and application of flow battery technology is limited by the performance of one of its core components, the diaphragm material. The diaphragm plays a vital role in flow batteries. It not only prevents the direct mixing of positive and negative electrolytes, but also allows ions to pass through to maintain charge balance. The ideal diaphragm material should have low resistance, high ion selectivity, good chemical and mechanical stability, and moderate cost.
[0004] Polybenzimidazole (PBI) membrane is a very representative diaphragm material on the market today. Due to its excellent chemical stability and unique ion conduction mechanism, it is considered to be one of the ideal choices for flow battery diaphragms. PBI materials can remain stable under extreme conditions (such as high temperature and strong acid environment), showing excellent chemical resistance and thermal stability. Despite this, PBI membranes still face many challenges in practical applications. First, its elongation at break needs to be improved to meet the needs of long-term operation of flow batteries. Secondly, the conductivity of the PBI membrane is closely related to battery performance, but it is often difficult to achieve optimal conductivity under traditional preparation methods. In addition, the procedure for preparing high-performance PBI membranes is complicated and costly, which largely limits its widespread application in commercial flow batteries.
[0005] In order to solve these problems, the industry continues to explore new membrane materials and preparation methods. For example, by introducing nanofillers into PBI membranes to improve their physical and electrochemical properties, or developing new chemical cross-linking methods to enhance the mechanical strength and stability of the membrane. Although these methods have improved the performance of the membrane to a certain extent, they still face problems such as high cost, complex preparation steps, and difficulty in large-scale production. Summary of the invention
[0006] The technical problem to be solved by the present invention is that the existing polybenzimidazole (PBI) membrane material has poor elongation at break, low electrical conductivity and difficult preparation method. The shortcomings and defects mentioned in the above background technology are overcome, and a cross-linked polybenzimidazole membrane and its preparation method and application are provided.
[0007] In order to solve the above technical problems, the technical solution proposed by the present invention is: A cross-linked polybenzimidazole film, wherein the cross-linked polybenzimidazole film comprises a three-dimensional network structure; The raw materials of the cross-linked polybenzimidazole film include polybenzimidazole, a cross-linking agent and a pore-forming agent. The cross-linking agent is a diepoxy compound or a silane coupling agent with an epoxy bond. The addition amount of the cross-linking agent relative to the polybenzimidazole is 2wt%-10wt%.
[0008] The present invention selects polybenzimidazole, a crosslinking agent and a pore-forming agent. The pore-forming agent generates micropores in the membrane to reduce the microscopic thickness of the polybenzimidazole and improve the proton conductivity of the polybenzimidazole. The crosslinking agent and the pore-forming agent are used in combination to produce a synergistic effect. Crosslinking is first performed and then pores are formed. When the pore-forming agent is precipitated by the solvent to form pores, the pore structure can be maintained, the shrinkage of the pores is reduced, and a three-dimensional network structure is formed.
[0009] The three-dimensional network structure of the cross-linked polybenzimidazole membrane helps to improve the mechanical strength of the membrane, prevent the cross-linking of active substances in the electrolyte, and reduce the water migration caused by the cross-linking of active substances in the electrolyte.
[0010] The cross-linked polybenzimidazole film prepared by the raw materials of the present invention has excellent electrical properties and high mechanical strength, and the cross-linking agent and polybenzimidazole can be selected according to application requirements, and the application range is wide; when the cross-linking agent is a diepoxy compound, the nitrogen atoms on the polybenzimidazole will chemically bond with the broken epoxy groups at high temperature to form a cross-linked structure. The following is a chemical bonding mechanism using polyethylene glycol diglycidyl ether as a reaction.
[0011]
[0012] The amount of 2-10% crosslinking agent is slightly excessive relative to the molar mass of PBI, and the excess can ensure the high degree of crosslinking of PBI as much as possible. However, too high a dosage of crosslinking agent will make the membrane brittle, so it is necessary to select a suitable amount of crosslinking agent to ensure the smooth crosslinking reaction.
[0013] The silane coupling agent needs to complete the above-mentioned process of chemical bonding between the nitrogen atom and the broken epoxy group when heated. After this process, it needs to be hydrolyzed in an acidic liquid flow battery to form a cross-linked structure. The hydrolysis must be under acidic conditions. Therefore, when the cross-linking agent is a silane coupling agent with an epoxy bond, the cross-linked polybenzimidazole membrane of the present application is suitable for acidic liquid flow batteries.
[0014] Preferably, the polybenzimidazole includes at least one of poly 2,2'-(1,4-naphthyl)-5,5'-bibenzimidazole (nPBI), poly 2,2'-(meta-phenyl)-5,5'-bibenzimidazole (mPBI), poly 2,2'-(p-phenyl)-5,5'-bibenzimidazole (pPBI) or poly 2,2'-(p-diphenylether)-5,5'-bibenzimidazole (OPBI), and the solid content is 8-20%.
[0015] Preferably, the diepoxide compound includes one or more of 1,7-octadiene diepoxide, 9,9-bis(4-epoxypropyloxyphenyl)fluorene, polyethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, bisphenol A diglycidyl ether, 1,4-bis(2',3'-epoxypropyl)perfluorobutane, aralkylphenol type epoxy resin, and trifunctional epoxy resin; The silane coupling agent having an epoxy bond includes 3-glycidyloxypropyltrimethoxysilane.
[0016] Preferably, the pore-forming agent includes one or more of glucose (GLU), lactose or polyethylene glycol (PEG), polyvinyl pyrrolidone (PVP) or fructose. The amount of pore-forming agent added relative to polybenzimidazole is 50wt%-125wt%. The selection of different pore-forming agents and different cross-linking agents is related to the electrochemical internal resistance and mechanical strength of the PBI membrane itself. The presence of the pore-forming agent enables the cross-linking agent to first cross-link the porous PBI structure to be washed out, thereby realizing the preparation of a cross-linked polybenzimidazole membrane with a three-dimensional network structure.
[0017] Preferably, when preparing the cross-linked polybenzimidazole membrane, polybenzimidazole, a cross-linking agent and a pore-forming agent are first mixed to form a membrane, and then the membrane is cross-linked by heating.
[0018] The cross-linking agent selected in the present application can directly complete cross-linking by only one step of heating during film formation, and the preparation method is simple. When the pore-forming agent is subsequently washed out, the shrinkage problem of pores in the porous membrane structure can be slowed down, thereby stabilizing the pore structure.
[0019] Under the same technical concept, the present invention also provides a method for preparing the cross-linked polybenzimidazole film, comprising the following steps: (1) preparing a polybenzimidazole solution with polybenzimidazole, a crosslinking agent and a pore-forming agent, and stirring the solution uniformly; (2) The mixed solution is prepared into a film, dried, heated for cross-linking, cooled and washed to obtain a cross-linked polybenzimidazole film.
[0020] The present application configures the polybenzimidazole solution, the crosslinking agent and the pore-forming agent together as a solution, which can omit the soaking step, greatly compress the production space and simplify the production equipment. After the film is prepared, the curing effect of the crosslinking agent can slow down the pore shrinkage problem after the pore-forming agent is subsequently removed, avoiding the decrease in the porosity of the porous film caused by shrinkage and the decrease in the proton conductivity of the membrane.
[0021] Preferably, the drying temperature in step (2) is 60-100°C, and the heating cross-linking temperature is 80-200°C. The cooling washing is to immerse the cross-linked polybenzimidazole membrane in water for 24-96 hours. The drying temperature controls the residual solvent content in the membrane, and the cross-linking time and the cross-linking temperature jointly control the cross-linking degree. The drying and cross-linking temperatures selected in this application can ensure that the prepared polybenzimidazole solution has good mechanical strength and cross-linked network structure.
[0022] Preferably, the film preparation method in step (2) includes one or more of blade coating, spin coating, solution casting, solution casting, melt extrusion or phase separation.
[0023] Under the same technical concept, the present invention also provides an application of a cross-linked polybenzimidazole membrane, wherein the cross-linked polybenzimidazole membrane is used as a diaphragm in a liquid flow battery.
[0024] Preferably, the flow battery includes one or more of an all-vanadium flow battery, an all-iron flow battery, a sulfur / iron flow battery, a zinc / iron flow battery, a zinc / bromine flow battery, a zinc / iodine flow battery, an iron / chromium flow battery or a vanadium / bromine flow battery.
[0025] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention proposes a cross-linked polybenzimidazole membrane with high mechanical strength, good mechanical stability, low swelling rate in electrolyte and high durability; the cross-linking agent and pore-forming agent selected in the present application can ensure that the cross-linked polybenzimidazole membrane forms a cross-linked network structure.
[0026] (2) The preparation method of the cross-linked polybenzimidazole membrane proposed in the present invention overcomes the complicated procedures of the prior art, simplifies the preparation process and improves the performance of the membrane, eliminates the traditional process of preparing a cross-linking agent solution-immersing reaction-cleaning-drying, and greatly simplifies the production and preparation process. The method has a fast membrane preparation speed and is conducive to roll-to-roll continuous production, thereby obtaining a variety of cross-linked polybenzimidazole membranes. At the same time, after the cross-linked polybenzimidazole membrane is cast, it is first cross-linked and then pore-formed. During the cross-linking process, the membrane is solidified, so the shrinkage degree of the pores is reduced during the cleaning stage, and the porosity and proton conductivity of the membrane are maintained. This method can significantly improve the electrochemical performance and mechanical stability of the PBI membrane, and is expected to play an important role in the commercial application of liquid flow batteries; (3) The liquid flow battery using the cross-linked membrane of the present invention has excellent electrical performance, high coulombic efficiency (above 99%) and high energy efficiency (above 72%). BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 It is a test graph of 300-cycle discharge capacity retention rate of the cross-linked polybenzimidazole membranes of Examples 1-6 of the present invention and Comparative Examples 1-2; Figure 2 300-cycle coulomb efficiency test graph of the cross-linked polybenzimidazole membranes of Examples 1-6 of the present invention and Comparative Examples 1-2; Figure 3 300 cycles of cycle efficiency test graph of the cross-linked polybenzimidazole membranes of Examples 1-6 of the present invention and Comparative Examples 1-2; Figure 4 is the cross-sectional SEM image of pure pPBI membrane; Figure 5 This is a SEM image of the porous cross-section of the cross-linked polybenzimidazole membrane of Example 2 of the present invention. DETAILED DESCRIPTION
[0029] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0030] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0031] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0032] Example 1 This embodiment provides a cross-linked polybenzimidazole membrane, which comprises a cross-linked network structure; the raw materials of the cross-linked polybenzimidazole membrane include 30g pPBI, 279g DMAc, 15g GLU, 7.5g PEG, and 0.9g aralkylphenol type epoxy resin.
[0033] The preparation method of the cross-linked polybenzimidazole film is as follows: (1) Weigh 30 g of pPBI, 279 g of DMAc, 15 g of GLU, 7.5 g of PEG, and 0.9 g of aralkylphenol-type epoxy resin and stir and mix at 60° C. for 48 h to obtain a polybenzimidazole solution; (2) Place the polybenzimidazole solution in a vacuum drying oven for 2 hours to remove the condensation. Pour the polybenzimidazole solution onto a coating plate, use a scraper to apply the polybenzimidazole to form a film, and dry it at 80°C for 24 hours. Heat it to 160°C for cross-linking for 3 hours. Soak the film in water for 96 hours to remove GLU and PEG, and obtain a cross-linked PBI membrane.
[0034] Example 2 This embodiment provides a cross-linked polybenzimidazole membrane, which comprises a cross-linked network structure; the raw materials of the cross-linked polybenzimidazole membrane include 30g pPBI, 279g DMAc, 15g GLU, 7.5g PEG, and 1.8g aralkylphenol type epoxy resin; Figure 5 3 is a SEM image of a porous cross-section of the cross-linked polybenzimidazole membrane of Example 2 of the present invention, from which it can be seen that the cross-linked polybenzimidazole membrane has a loose and porous cross-linked network structure. Figure 4 This is the SEM image of the cross section of pure pPBI membrane.
[0035] The preparation method of the cross-linked polybenzimidazole film is as follows: (1) 30 g of pPBI, 279.9 g of DMAc, 15 g of GLU, 7.5 g of PEG, and 1.8 g of aralkylphenol-type epoxy resin were weighed and stirred at 60° C. for 48 h to obtain a polybenzimidazole solution.
[0036] (2) Place the polybenzimidazole solution in a vacuum drying oven for 2 hours to remove the condensation. Pour the polybenzimidazole solution onto a coating plate, use a scraper to apply the polybenzimidazole to form a film, and dry it at 80°C for 24 hours. Heat it to 160°C for cross-linking for 3 hours. Soak the film in water for 96 hours to remove GLU and PEG, and obtain a cross-linked pPBI membrane.
[0037] Example 3 This embodiment provides a cross-linked polybenzimidazole membrane, which comprises a cross-linked network structure; the raw materials of the cross-linked polybenzimidazole membrane include 30g pPBI, 279g DMAc, 15g PEG, 7.5g PVP, and 1.8g 1,7-octadiene diepoxide; The preparation method of the cross-linked polybenzimidazole film is as follows: (1) Weigh 30 g of pPBI, 279 g of DMAc, 15 g of PEG, 7.5 g of PVP, and 1.8 g of 1,7-octadiene diepoxide and stir and mix them at 60° C. for 48 h to obtain a polybenzimidazole solution.
[0038] (2) Place the polybenzimidazole solution in a vacuum drying oven for 2 hours to remove vacuuum and foam. Pour the polybenzimidazole solution onto a coating plate, use a scraper to apply the polybenzimidazole to form a film, and dry it at 80°C for 24 hours. Heat it to 160°C for crosslinking for 3 hours, and soak the film in water for 96 hours to remove PEG and PVP, thereby obtaining a crosslinked pPBI membrane.
[0039] Example 4 The present embodiment provides a cross-linked polybenzimidazole membrane, which comprises a cross-linked network structure; the raw materials of the cross-linked polybenzimidazole membrane include 30g pPBI, 279g DMAc, 15g PEG, 7.5g PVP, and 1.8g 9,9-bis(4-epoxypropyloxyphenyl)fluorene.
[0040] The preparation method of the cross-linked polybenzimidazole film is as follows: (1) Weigh 30 g pPBI, 279 g DMAc, 15 g PEG, 7.5 g PVP, and 1.8 g 9,9-bis(4-epoxypropyloxyphenyl)fluorene and stir and mix at 60°C for 48 h to obtain a polybenzimidazole solution. Place the polybenzimidazole solution in a vacuum drying oven for 2 h to evacuate and defoam.
[0041] (2) Pour the polybenzimidazole solution onto a coating plate, use a scraper to coat the polybenzimidazole into a film and dry it at 80°C for 24 hours, heat it to 160°C for cross-linking for 3 hours, and soak the film in water for 96 hours to remove PEG and PVP, thereby obtaining a cross-linked pPBI membrane.
[0042] Example 5 This embodiment provides a cross-linked polybenzimidazole membrane, which comprises a cross-linked network structure; the raw materials of the cross-linked polybenzimidazole membrane include 30g pPBI, 279g DMAc, 15g PEG, 7.5g PVP, and 1.8g polyethylene glycol diglycidyl ether.
[0043] The preparation method of the cross-linked polybenzimidazole film is as follows: (1) Weigh 30 g pPBI, 279 g DMAc, 15 g PEG, 7.5 g PVP, and 2.7 g polyethylene glycol diglycidyl ether and stir and mix at 60°C for 48 h to obtain a polybenzimidazole solution. Place the polybenzimidazole solution in a vacuum drying oven for 2 h to evacuate and defoam.
[0044] (2) Pour the polybenzimidazole solution onto a coating plate, use a scraper to coat the polybenzimidazole into a film and dry it at 80°C for 24 hours, heat it to 160°C for cross-linking for 3 hours, and soak the film in water for 96 hours to remove PEG and PVP, thereby obtaining a cross-linked pPBI membrane.
[0045] Example 6 This embodiment provides a cross-linked polybenzimidazole membrane, which comprises a cross-linked network structure; the raw materials of the cross-linked polybenzimidazole membrane include 30g pPBI, 279g DMAc, 15g PEG, 7.5g PVP, and 1.8g 3-glycidyloxypropyltrimethoxysilane.
[0046] The preparation method of the cross-linked polybenzimidazole film is as follows: (1) Weigh 30 g pPBI, 279 g DMAc, 15 g PEG, 7.5 g PVP, and 1.8 g 3-glycidyloxypropyltrimethoxysilane and stir and mix at 60° C. for 48 h to obtain a polybenzimidazole solution. Place the polybenzimidazole solution in a vacuum drying oven for 2 h to evacuate and defoam.
[0047] (2) Pour the polybenzimidazole solution onto a coating plate, use a scraper to coat the polybenzimidazole into a film and dry it at 80°C for 24 h, heat it to 160°C for cross-linking for 3 h, and soak the film in 1 M dilute sulfuric acid at 70°C for 24 h to complete the hydrolysis and remove PEG and PVP, thereby obtaining a cross-linked pPBI membrane.
[0048] Comparative Example 1 This comparative example provides a polybenzimidazole membrane. The raw materials of the polybenzimidazole membrane include 30g pPBI, 311.6g DMAc, 15g GLU, 7.5g PEG, and α,α′-dibromo-p-xylene (DBX).
[0049] The preparation method of the cross-linked polybenzimidazole film is as follows: Weigh 30g pPBI, 311.6g DMAc, 15g GLU, and 7.5g PEG and stir and mix at 60°C for 48h to obtain a polybenzimidazole solution. Place the polybenzimidazole solution in a vacuum drying oven for 2h to evacuate and defoam. Pour the polybenzimidazole solution onto a scraping board, scrape the polybenzimidazole into a film with a scraper, and dry at 80°C for 24h to obtain a pPBI film.
[0050] A 6 wt% crosslinker solution was prepared by dissolving DBX in acetonitrile. The pPBI membrane was then immersed in the crosslinking solution at 80°C for 24 hours with continuous stirring and reflux. Afterwards, the membrane was rinsed with isopropanol to remove any residual chemicals.
[0051] Comparative Example 2 This embodiment provides a cross-linked polybenzimidazole membrane, which comprises a cross-linked network structure; the raw materials of the cross-linked polybenzimidazole membrane include 30g pPBI, 279g DMAc, 15g GLU, 7.5g PEG, and 2.7g aralkylphenol type epoxy resin.
[0052] The preparation method of the cross-linked polybenzimidazole film is as follows: (1) Weigh 30 g pPBI, 279 g DMAc, 15 g GLU, 7.5 g PEG, and 1.8 g aralkylphenol epoxy resin and stir and mix at 60°C for 48 h to obtain a polybenzimidazole solution. Place the polybenzimidazole solution in a vacuum drying oven for 2 h to evacuate and defoam.
[0053] (2) Pour the polybenzimidazole solution onto a coating plate, use a scraper to coat the polybenzimidazole into a film and dry it at 80°C for 24 h. Soak the film in water for 96 h to remove GLU and PEG. After drying at 50°C, heat it to 160°C for cross-linking for 3 h to obtain a cross-linked pPBI membrane.
[0054] The proton conductivity test of the polybenzimidazole membranes obtained in Examples 1-6 and Comparative Examples 1-2 was performed. The proton conductivity test steps are as follows: The proton conductivity of the polymer membrane was evaluated using an electrochemical workstation. The three-electrode AC impedance method was performed at 100% relative humidity, with a test frequency of 10kHz-80kHz, an amplitude of 5mV, a test temperature of 25°C, and a sample size of not less than 1cm*1cm. The proton conductivity of the membrane material was calculated using the following formula:
[0055] Where R is the surface resistance of the membrane (Ω). For the measurement of proton conductivity, L is the thickness of the membrane (cm) and A is the effective area of the membrane (cm 2 ).
[0056] The obtained proton conductivity test data is shown in Table 1.
[0057] Table 1. Proton conductivity test data
[0058] From the comparison between Comparative Example 1 and Examples 3-6, it can be seen that the method of directly heating, cross-linking and then forming pores is relatively higher in proton conductivity than forming pores first and then cross-linking by solution immersion. From Examples 1-6, it can be seen that as the amount of cross-linking agent used increases, the degree of cross-linking of the membrane increases, the proton conductivity will decrease accordingly, the tensile strength will increase accordingly, and the elongation at break will decrease. From Comparative Example 2, it can be seen that if the pore-forming agent is washed away first and then heated for cross-linking, the shrinkage of the pores of the porous PBI membrane will be accelerated, resulting in a decrease in proton conductivity, an increase in tensile strength, and a decrease in elongation at break. In Comparative Example 2, after the pore-forming agent is washed out first, the membrane is cross-linked at 160°C, the film shrinks sharply, the porosity decreases, and the thickness decreases to 17μm. The proton conductivity is close to that of pure PBI due to the porosity decreases to a very low level, and the tensile strength and elongation at break are also relatively low.
[0059] The polybenzimidazole membrane obtained in Examples 1-6 and Comparative Examples 1-2 was used as a diaphragm to prepare an all-vanadium liquid flow battery. The battery system consisted of a membrane, a carbon felt electrode, a rubber gasket, a flow channel plate, a current collecting plate, an end plate, an electrolyte, and a circulation pump. The single-side electrolyte volume was 450 ml. The battery test steps were as follows: For the charge and discharge tests, the cut-off voltages for charge and discharge were 1.6 V and 1.0 V, respectively, and the constant current density for the test was 180 mA cm -2 The test cycle is 300 cycles. The battery test data obtained by the test is as follows Figure 1 , Figure 2 , Figure 3 shown.
[0060] From the comparison of comparative example 1 and examples 1-6, it can be seen that due to the overall influence of cross-linking and shrinkage, although the capacity attenuation of comparative example 1 is small, the capacity value is low in examples 1-6. It can be seen from examples 1-2 that as the amount of cross-linking agent added gradually increases, the degree of cross-linking of the membrane increases, and the capacity retention rate of the battery within 300 cycles will increase accordingly, that is, the attenuation of the PBI membrane in the battery will decrease accordingly, and it can be seen from examples 2-6 that different types of cross-linking agent structures also have an effect on capacity, capacity retention rate, and energy efficiency. From the data, it can be seen that the rigid long-chain cross-linking agent represented by aralkylphenol epoxy resin can achieve the best effect. Due to the Donnan exclusion effect of the PBI membrane itself, the coulomb efficiency is maintained at a high level in both the comparative example and the example.
[0061] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A cross-linked polybenzimidazole film, characterized in that: The cross-linked polybenzimidazole membrane comprises a cross-linked network structure; The main raw materials of the cross-linked polybenzimidazole membrane include polybenzimidazole, a cross-linking agent, and a pore-forming agent. The cross-linking agent is a diepoxide compound or a silane coupling agent with an epoxy bond. The addition amount of the cross-linking agent relative to the polybenzimidazole is 2wt%-10wt%.
2. The cross-linked polybenzimidazole film according to claim 1, characterized in that The polybenzimidazole includes at least one of poly 2,2'-(1,4-naphthyl)-5,5'-bibenzimidazole, poly 2,2'-(m-phenyl)-5,5'-bibenzimidazole, poly 2,2'-(p-phenyl)-5,5'-bibenzimidazole or poly 2,2'-(p-diphenylether)-5,5'-bibenzimidazole.
3. The cross-linked polybenzimidazole film according to claim 1, characterized in that The diepoxide compound includes one or more of 1,7-octadiene diepoxide, 9,9-bis(4-epoxypropyloxyphenyl)fluorene, polyethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, bisphenol A diglycidyl ether, 1,4-bis(2',3'-epoxypropyl)perfluorobutane, aralkylphenol type epoxy resin, and trifunctional epoxy resin; The silane coupling agent having an epoxy bond includes 3-glycidyloxypropyltrimethoxysilane.
4. The cross-linked polybenzimidazole film according to claim 1, characterized in that: The pore-forming agent includes one or more of glucose, lactose, polyethylene glycol, polyvinyl pyrrolidone or fructose, and the added amount of the pore-forming agent relative to polybenzimidazole is 50wt%-125wt%.
5. The cross-linked polybenzimidazole film according to claim 1, characterized in that: When preparing the cross-linked polybenzimidazole membrane, polybenzimidazole, a cross-linking agent and a pore-forming agent are first mixed to form a membrane, and then the membrane is cross-linked by heating.
6. A method for preparing a cross-linked polybenzimidazole film according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) preparing a polybenzimidazole solution with polybenzimidazole, a crosslinking agent and a pore-forming agent, and stirring the solution uniformly; (2) The mixed solution is prepared into a film, dried, heated for cross-linking, cooled and washed to obtain a cross-linked polybenzimidazole film.
7. The preparation method according to claim 6, characterized in that: In step (2), the drying temperature is 60-100°C, the drying time is 4-48h, the heating cross-linking temperature is 80-200°C, the heating cross-linking time is 1-4h, and the cooling washing is to immerse the cross-linked polybenzimidazole membrane in water for 24-96h.
8. The preparation method according to claim 6, characterized in that: The film preparation method in step (2) includes one or more of blade coating, spin coating, solution casting, solution casting, melt extrusion or phase separation.
9. An application of the cross-linked polybenzimidazole membrane according to any one of claims 1 to 5, characterized in that: The cross-linked polybenzimidazole membrane is used as a diaphragm in a liquid flow battery.
10. The use according to claim 9, characterized in that The flow battery includes one or more of an all-vanadium flow battery, an all-iron flow battery, a sulfur / iron flow battery, a zinc / iron flow battery, a zinc / bromine flow battery, a zinc / iodine flow battery, an iron / chromium flow battery or a vanadium / bromine flow battery.
Citation Information
Cited By
Cross-linked sulfonated polybenzimidazole membrane as well as preparation method and application thereof
CN120098302A
Polybenzimidazole modified ion conducting membrane for flow battery and preparation method of polybenzimidazole modified ion conducting membrane
CN121181962A